Degrading Penal Populism Through Alternative Sanctions in The Indonesian Penal Code - Ahwan Ahwan; Ika Yuliana Susilawati (Civiliza Publishing, 2026)
The enactment of the Penal Code (Law No. 1/2023) marks a historic shift in national penal policy, revealing a complex dualism between retributive penal populism and modern sentencing moderation. This paper aims to analyze the structure of penal policy within the Penal Code to examine how alternative sanctions are normatively designed to control, limit, and degrade the expansive destructive power of penal populism. Employing a doctrinal legal research method with legislative, conceptual, and legal-historical approaches, this study examines how the New Penal Code exhibits a “Janus-faced penal policy.” On one hand, this codification accommodates public punitive sentiment through the retention of the death penalty, the expansion of overcriminalization in public spaces, and intervention in the private sphere. On the other hand, however, it institutionalizes balancing mechanisms through the incorporation of new alternative sanctions, namely probation and community service. Guided by the “Principle of Balance” enshrined in the sentencing guidelines (Articles 51–54), these alternative sanctions function as a safety valve. This study concludes that the convergence of these two opposing paradigms is not merely a forced pragmatic political compromise, but rather a systemic normative design intended to curb the public’s punitive zeal while simultaneously preventing the judicial system from collapsing due to prison overcrowding. The success of this de-escalation of penal populism ultimately rests on the standardization of judicial risk assessment tools and a progressive shift in the mindset of law enforcement officials.